SUPPLY CHAIN AGILITY: A MEASUREMENT MODEL - Martins, A.; Crespo de Carvalho, J.; Menezes, J.; Dias, E.B. (5th International Meeting for Research on Logistics, 2004)
Agility and agile supply chain are increasingly mentioned in literature. Measurement attempts have been rehearsed but no stabilised model of evaluation has yet been reached. The purpose of this paper is to develop a four-dimension model to analyse agility performance levels of organizations and classify strategies according to the level of importance given to each of those dimensions. Through literature review four main dimensions are identified to an agile supply chain: market sensitivity, virtualisation, process integration and network based. From this dimensions a scale is developed and used to define underperformance behaviours and each one of those behaviours is characterized independently. The model is be used to exemplify the need to continuously adjust the agility level of the organization to changes in demand. Findings allow affirming that maximum performance is unreachable as changes in demand are continuous, thus the need to continuously adjust to those changes. Limitations to the results are identified as well as topics for further research.